Datering av röta i hålekar - Roswall, Joakim (SLU/Southern Swedish Forest Research Centre, 2006)
I have chosen in this work to examine which factors are affecting the artificially creation of a tree cavity containing decomposed wood. The purpose of the work is to find out which factors are affecting the most when a tree cavity is created, and to apply these results when you artificially try to create a tree cavity. The need to create tree cavities comes from the situation where many tree cavity living beetles finds themselves today. When existing trees are to pass out there will be no suitable inheritors yet. The work was initially to focus on cavities created from cut branches. The lack of proper examinations materials forced me to work on naturally dead branches. The field work has consisted of searching for oaktrees with cavities. These have then been examined and if they were suitable, data and samples were collected from them. The wood covering that results from a branch death has given us the date for the very start of the tree cavity. Whether these results apply to tree cavities created from cut branches is uncertain, perhaps the results are more to be regarded as a pointer to which trees/ branches where focus should be put in such a measure. The work shows yet what time perspective which is current when it comes to naturally created tree cavities.